A generic surfactant-free approach to overcome wetting limitations and its application to improve inkjet-printed P3HT:non-fullerene acceptor PV. Issue 21 (14th May 2019) - Maisch, Philipp; Eisenhofer, Lena M.; Tam, Kai Cheong; Distler, Andreas; Voigt, Monika M.; Brabec, Christoph J.; Egelhaaf, Hans-Joachim
Abstract : A novel strategy to overcome wetting problems is applied to manufacture inverted structure P3HT:O-IDTBR solar cells with 5% efficiency. Abstract : Solution based thin film technology often implies challenging wetting behaviour which has to be improved in order to achieve good printing or coating qualities. A common way of solving such problems is the use of wetting agents but they often show undesired side effects. In this work, we introduce a generic strategy to overcome this problem. We demonstrate inkjet printed arrays of poly(3, 4-ethylenedioxythiophene)-polystyrene sulfonate (PEDOT:PSS) dots to efficiently pin the three-phase contact line of wet films, thereby enforcing homogenous wetting and subsequent drying on low energetic surfaces. By printing and drying single droplets of ink, a matrix of anchoring points is created which pins the subsequently printed continuous wet layer and thus enables the coating of large surface areas with homogeneous, defect free films. This method also allows convenient patterning of surfaces by combining inkjet-printing of anchoring points with subsequent large area flood coating, e.g., by doctor blading. Furthermore, the defined placement of each anchoring point allows full thermodynamic control of the film formation by quantitative calculation of the processing windows and patterning precision. The beneficial application of this new strategy to printed electronics is demonstrated by fabricating organic solar cells with power conversion efficiencies of 5%. This is achieved by printing a hydrophilic PEDOT:PSS electron blocking layer without addition of surfactants at unprecedented quality onto an otherwise non-wettable hydrophobic active layer consisting of poly(3-hexylthiophene) (P3HT) and the indacenodithiophene-based non-fullerene acceptor O-IDTBR.